AN ANALYSIS OF THE READINESS OF IT SPECIALTIES STUDENTS TO USE INFORMATION TECHNOLOGY IN THE EDUCATIONAL PROCESS - Denysenko, Veronika; Vinnyk, Maksym; Tarasich, Yulia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The development of ICT and globalization of education create new educational competitive environment which feature is the information communication technology and student mobility. So today, it is important not only the technical support of the educational process, but also the level of students’ readiness to use advanced information technology as one of the basic educational facility of information and communication teaching environment in higher educational establishments. In this regard, the main objectives of the paper are the analysis and display of the obtained results of research of IT specialties students' readiness of Ukrainian universities to use information technology in the educational process.